2020
DOI: 10.1038/s41598-020-59563-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of electric conduction mechanisms in bismuth silicate nanofibers

Abstract: This work represents the nature of conduction mechanism in bismuth silicate (BiSiO) nanofibers as a function of temperature and frequency. Scanning electron micrographs and X-rays diffraction patterns exhibited the formation of cubic phases of Bi 4 (Sio 4 ) 3 and Bi 12 Sio 20 nanofibers respectively with an average diameter of ~200 nm. Temperature dependent (300 K-400 K) electrical characterization of fibers was carried out in frequency range of ~20 Hz-2 MHz. The complex impedance analysis showed contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A similar type of behaviour has been reported for bismuth-based ceramic glasses. 52,53 The variation of AC conductivity as a function of temperature was analysed using Jonscher's universal power law, σ AC = σ DC + A ( T ) ω S …, where A is the temperature-dependent factor associated with the polarizability strength of the material and ‘ S ’ is the frequency-dependent parameter, which varies between 0 and 1. The parameter ‘ S ’ has been used to determine the conductivity mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar type of behaviour has been reported for bismuth-based ceramic glasses. 52,53 The variation of AC conductivity as a function of temperature was analysed using Jonscher's universal power law, σ AC = σ DC + A ( T ) ω S …, where A is the temperature-dependent factor associated with the polarizability strength of the material and ‘ S ’ is the frequency-dependent parameter, which varies between 0 and 1. The parameter ‘ S ’ has been used to determine the conductivity mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…A similar type of behaviour has been reported for bismuth-based ceramic glasses. 52,53 The variation of AC conductivity as a function of temperature was analysed using Jonscher's universal power law,…”
Section: Papermentioning
confidence: 99%
“…[ 6–14 ] It is used for two‐wave mixing, four‐wave mixing, phase conjugation, real‐time holography, optical data storage, optical computing, and electro‐optical modulation. [ 7,8 ]…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Among sillenites, bismuth silicate (Bi 12 SiO 20 , BSO) is a technologically important material as it exhibits large electro-optic and photoconductive effects, which make it suitable for optical switches, optics-based electric field sensors, holographic storage, and photorefractive devices. [6][7][8][9][10][11][12][13][14] It is used for two-wave mixing, four-wave mixing, phase conjugation, real-time holography, optical data storage, optical computing, and electro-optical modulation. [7,8] It has been reported that the photorefractive property of BSO is enhanced significantly on doping with metals like Cr, Fe, Mg, Ru, etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation